Dynamics of markers of lipid metabolism during combined preventive therapy of pregnant women with obesity and reduced vitamin D status - O.V. Bulavenko; О.V. Bodnarchuk; O.M. Honcharenko; S.М. Kosianenko; D.H. Konkov (Publishing House TRILIST, 2022)
Objectives: to evaluate the effectiveness of multidose supplementation of vitamin D on the dynamics of serum levels of markers of lipid metabolism in pregnant women with obesity. Materials and methods. The study included 75 pregnant women with the І degree of obesity and low vitamin D status, who were divided into subgroups depending on the vitamin D dose of and the baseline 25(OH)D level in blood serum: I subgroup - 24 women with 25(OH)D less than 22.0 ng/ml who received Decristol 4000 IU/day; II subgroup - 26 pregnant women with 25(OH)D = 22.1-28.0 ng/ml who received Decristol 2000 IU/day; III subgroup - 25 patients with 25(OH)D over 28.1 ng/ml, who received 1000 IU of vitamin D per day. Pregnant women of all these subgroups also took acetylsalicylic acid at a dose of 100 mg/day. The control group included 26 practically healthy women who received 600 IU of vitamin D per day. Serum adipokinins levels were studied at 11-13, 22-24 and 31-33 weeks of gestation. Results. Significant differences were found in the increase of leptin (p < 0.0001) and resistin (p < 0.0001) and the decrease of adiponectin (p = 0.006) in pregnant women with impaired vitamin D metabolism against the background of moderate obesity in the І trimester compared to the control group. A more positive effect was found for Decristol 4000 IU (patients with vitamin D deficiency), against the treatment of Decristol 2000 IU (patients with vitamin D deficiency). At 31-33 weeks of gestation, there was a statistically significant decrease in serum level of resistin (p = 0.006) and a similar increase in adiponectin (p = 0.025) in patients receiving vitamin D 4000 IU, compared with the same indicators in clinical subgroups. Resistin and adiponectin may be markers of perinatal pathology in obese pregnant women in the first trimester of gestation, in terms of specificity (91.5 and 78.7%, respectively), sensitivity (100.0 and 91.3%, respectively); positive probability (11.75 and 4.29%, respectively), negative prognostic value (100.0 and 94.9%, respectively) and test accuracy (94.3 and 82.9%, respectively). Conclusions. The use of markers of lipid metabolism as diagnostic criteria during pregnancy in women with the І degree of obesity and low vitamin D status has predictor and prognostic value for the risk of perinatal pathology and helps to assess the effectiveness of comprehensive prophylactic therapy.